Cheap talk? Financial sanctions and non-financial firms - Tibor Besedeš; Stefan Goldbach; Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2021)
Sanctions restrict cross-border interactions and therefore, not only put political and economic pressure on the target country, but also adversely affect the sender country. This paper examines the effect of financial sanctions on the country imposing them. We analyze the business responses of German non-financial entities to the imposition of sanctions on 23 countries over the period from 1999 through 2014. Examining highly disaggregated, monthly data from the German balance of payments statistics, we find four main results. First, German financial activities with sanctioned countries are reduced after the imposition of sanctions. Second, firms doing business with sanctioned countries tend to be disproportionately large, often having alternative business opportunities. Third, firms affected by sanctions expand their activities with non-sanctioned countries, some of which display close trade ties to the sanctioned country. Fourth, we find no effect of sanctions on broader measures of firm performance such as employment or total sales. Overall, we conclude that the economic costs of financial sanctions to the sender country are limited.
urn:nbn:de:tuda-tuprints-176312
Keywords: F20; F36; F38; F51; 330; sanction; restriction; cross-border transaction